Satellite-Based Precipitation Estimation for Hydropower Development - Tamrakar, Bijaya; Alfredsen, Knut (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
Runoff is one of the major factors that govern the capacity of a hydropower project. Precipitation data are needed for estimation of runoff through runoff simulation using a hydrological model. Dense setup of rain gauge network in a mountainous topography is difficult and expensive. An alternative for this problem is the use of Satellite precipitation data with high spatial and temporal resolution. They have an additional advantage that they represent areal precipitation. But, these data should be duly evaluated before using them. In this study, Tropical Rainfall Measuring Mission (TRMM 3B42) precipitation data are evaluated using ground based precipitation stations over Nepal and fed in a rainfall-runoff model to estimate monthly discharge through four of the major basins of Nepal. A simple water balance model has been used, initially developed by Thornthwaite. Statistical parameters showed significant under-estimation of precipitation over major areas of Nepal. The results from the water balance model presented quiet a good estimation of discharge through basins with an average Nash Sutcliffe Efficiency (R²) value of 0.8. This implies that TRMM data can be used for runoff simulations over Nepal. The TRMM satellite data can be used during the planning stage of hydropower projects as well as on ungauged catchments. Hydro Nepal: Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 52-58 DOI: http://dx.doi.org/10.3126/hn.v12i0.9033 Uploaded Date : 10/29/2013